Titanium-doped hydroxyapatites photoanodes for Dye-Sensitized Solar Cells. Issue 7 (1st April 2021) - Sangiorgi, Nicola; Bendoni, Riccardo; Sangiorgi, Alex; Aversa, Lucrezia; Tatti, Roberta; Verucchi, Roberto; Adamiano, Alessio; Sandri, Monica; Tampieri, Anna; Sanson, Alessandra
Abstract: The development of new materials based on abundant elements, reduced toxicity is today crucial for the next generation of energy device. Titanium-doped hydroxyapatite (TiHA) was tested for the first time as photoanode material for Dye – Sensitized Solar Cells (DSSCs). The chemical composition and energy structure of TiHA powders with increasing titanium content (5 wt%, 10 wt% and 15 wt%) were extensively characterized by surface electron spectroscopies, XPS and UPS. Their compatibility with conventional ruthenium-based dyes molecules was also assessed, producing considerable uptake. TiHA films were produced by screen-printing technique and XRD analyses confirm the presence of apatitic structure. The film properties were completely determined by optical, morphological (FE–SEM) and functional characterizations. Finally, TiHA-based DSSCs were assembled and their photovoltaic performance were assessed. The best efficiency, equal to 0.14%, was obtained for the TiHA containing 15 wt% of titanium. These results open the path for the possible application of doped hydroxyapatite as novel materials for energy conversion systems.